Jordan K. answered • 05/22/13

Nationally Certified Math Teacher (grades 6 through 12)

From the problem we can see that both A and C can be expressed in terms of B:

A = B / 2

B = C / 2 or C = 2B

Now the average of A and B anc C is given as 70

Equation expressing the average: (A + B + C) / 3 = 70

Plugging in expressions for A and C in terms of B: (B/2 + B + 2B) / 3 = 70

Multiplying both sides of equation by 3: B/2 + B + 2B = 210

Multiplying both sides of equation by 2 to get rid of fraction on left side: B + 2B + 4B = 420

Combing B terms on left side: 7B = 420

Dividing both sides of equation by 7 to get value of B: B = 60

Plug in value for B in B expression for A: A = B / 2 = 60 / 2 = 30

Roman C.

11/01/12